The Resource Curse and Fiscal Policy Volatility - Michael Bleaney; Håvard Halland (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2009)
Using data from 1980 to 2004, we show that greater fiscal policy volatility acts as a transmission mechanism for the resource curse. Resource exports dominate political and institutional variables as determinants of fiscal policy volatility, with fiscal policy volatility being a significant determinant of growth. The existence of a resource curse is confirmed, in the sense that a higher ratio of natural resource exports to total merchandise exports is associated with significantly slower per capita GDP growth. There are no statistically significant differences between the effects of point-source and diffuse resource exports.
Keywords: H50; O40; Q33; 330; fiscal policy; growth; resource curse; Natürliche Ressourcen; Export; Finanzpolitik; Volatilität; Wirtschaftswachstum; Welt